Considerações contemporâneas sobre a natureza ética do homem conforme Tomás de Aquino (2019)
In face of contemporary difficulties in the foundation of ethical thought, mostly due to necessary but extrapolated fractures between nature and subjectivity, knowledge and action, many thinkers are now revisiting the great thomasian synthesis of western thought. Under many reinterpretations in the fields of ethics, law, epistemology and metaphysics, it is not improper to say that thomasian thought lives a small renaissance, particularly in the English-speaking world, resulting in numerous revisionistic and historical approaches, as much as adaptations in the research fields of analytic philosophy and theology. Avoiding the systematical analysis in favor of a simpler and more informative presentation we expose central tenets of thomasian ethics in close consideration to their metaphysical groundings, according to contemporary authors who struggle in this thomasian revival, making explicit the relevance of the moral disposition of human beings in this thought.